2020
DOI: 10.4103/ijo.ijo_1552_19
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcome of botulinum neurotoxin A injection with or without sodium hyaluronate in the treatment of infantile esotropia—a prospective interventional study

Abstract: Purpose: To compare the short-term outcome of botulinum neurotoxin A (BoNT-A) with or without sodium hyaluronate in the treatment of infantile esotropia (IE). Methods: In this tertiary care hospital-based prospective, interventional, non-randomized study on infants with IE below one year of age, 25 cases were enrolled in the sodium hyaluronate (SH) group to receive 2.5 U BoNT-A injection combined with SH in each medial rectus muscle (MR). Thirty patients were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…[ 1 ] Our study was conducted to assess the effect of combining Botulinum neurotoxin A (BoNT –A) with Sodium Hyaluronate (SH) in Indian children below 1 year with a simpler technique of preparation of injection. [ 2 ] The concentration of SH was same as used by Chen et al [ 3 ] We have demonstrated similar effectivity and address the concerns raised by the authors here.…”
supporting
confidence: 70%
“…[ 1 ] Our study was conducted to assess the effect of combining Botulinum neurotoxin A (BoNT –A) with Sodium Hyaluronate (SH) in Indian children below 1 year with a simpler technique of preparation of injection. [ 2 ] The concentration of SH was same as used by Chen et al [ 3 ] We have demonstrated similar effectivity and address the concerns raised by the authors here.…”
supporting
confidence: 70%
“…Pandey et al . [ 9 ] have successfully used this product for infantile esotropia. The authors of the present study in this journal issue have described their experience with the same product in the treatment of essential blepharospasm and hemifacial spasms.…”
mentioning
confidence: 99%
“…Pandey N and colleagues need to be commended for replicating, in Indian population, the study comparing outcomes of botulinum neurotoxin A injection with and without sodium hyaluronate (SH) in treating infantile esotropia (IET). [ 1 ] We would like to make certain observations. Chen and colleagues describe constitution of toxin-SH done at 4°C.…”
mentioning
confidence: 99%